Improving Regional Revenue Through Taxpayer Compliance: An Economic Study on Service Quality, Knowledge, and Sanctions in Buleleng - Sanjaya, Pattama Putta Laksmi; Suarmanayasa, I Nengah; Telagawathi, Ni Luh Wayan Sayang (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of service quality, tax knowledge, and tax sanctions on motor vehicle taxpayer compliance in Buleleng Regency. A quantitative approach was applied using a survey method, in which data were collected through questionnaires from 100 respondents selected by simple random sampling from a total population of 269,486 taxpayers. The data were analyzed using multiple linear regression. The findings indicate that service quality, knowledge, and tax sanctions simultaneously have a significant effect on taxpayer compliance. Individually, each variable also exerts a positive and significant influence on compliance. These results suggest that improving taxpayer compliance—as a strategy to enhance regional revenue—requires attention to service delivery, tax education, and the enforcement of effective sanctions.